Six-Minute walk distance predicts outcomes in liver transplant candidates. Issue 5 (25th May 2023) - Cox-Flaherty, Katherine; Moutchia, Jude; Krowka, Michael J.; Al-Naamani, Nadine; Fallon, Michael B.; DuBrock, Hilary; Forde, Kimberly A.; Krok, Karen; Doyle, Margaret F.; Kawut, Steven M.; Ventetuolo, Corey E.
Abstract : A 6-minute walk test is a simple tool for assessing submaximal exercise capacity. We sought to determine whether a 6-minute walk distance (6MWD) predicts outcomes in patients with cirrhosis. The Pulmonary Vascular Complications of Liver Disease 2 study is a multicenter, prospective cohort study that enrolled adults with portal hypertension during liver transplantation evaluation. We excluded subjects with an incident or prevalent portopulmonary hypertension. The 6-minute walk test was performed using standardized methods. Cox proportional hazards modeling and multivariable linear regression analysis were performed to determine the relationship between baseline 6MWD and outcomes. The study sample included 352 subjects. The mean 6MWD was 391±101 m. For each 50-meter decrease in 6MWD, there was a 25% increase in the risk of death (HR 1.25, 95% CI [1.11, 1.41], p < 0.001) after adjustment for age, gender, body mass index, MELD-Na, and liver transplant as a time-varying covariate. In a multistate model, each 50-meter decrease in 6MWD was associated with an increased risk of death before the liver transplant ( p < 0.001) but not after the transplant. 6MWD was similar to MELD-Na in discriminating mortality. Each 50-meter decrease in 6MWD was associated with an increase in all-cause ( p < 0.001) and transplant-free hospitalizations ( p < 0.001) in multivariable models for time-to-recurrent events. Shorter 6MWD was associated with worse Short Form-36 physical ( p < 0.001) and mental component scores ( p = 0.05). In conclusion, shorter 6MWD is associated with an increased risk of death, hospitalizations, and worse quality of life in patients evaluated for liver transplantation. The 6-minute walk distance may be a useful adjunct for risk assessment in patients undergoing liver transplant evaluation.